Mastering Windows 7 deployment - Finn, Aidan, 1974- (Serious skills., 2011)
Get professional-level instruction on Windows 7 deployment tools Enterprise-level operating system deployment is challenging and requires knowledge of specific tools. It is expected that Windows 7 will be extensively deployed in businesses worldwide. This comprehensive Sybex guide provides thorough coverage of the Microsoft deployment tools that were specifically created for Windows 7, preparing system administrators, MIS professionals, and corporate programmers to tackle the task effectively.Companies worldwide are expected to deploy Windows 7 as their enterprise operating system; system admi.